PENGARUH E-SERVICE QUALITY, BRAND IMAGE dan HARGA TERHADAP MINAT BELI KONSUMEN ONLINE SHOP BLIBLI.COM (Studi Kasus Konsumen Blibli.com UPN “Veteran” Jawa Timur) - Januar Reza, Ramadhan; rusdi, Hidayat (Jurnal Bisnis Indonesia, 2021)
This study aims to determine how the influence of E-Service Quality, BrandImage and Harga on Minat Beli Konsumen in Blibli.com Online Shop. In thiscase the researcher took a sample in the UPN "Veteran of East Java. The research method used is descriptive research with a quantitative approach.Data collection techniques through the distribution of questionnaires torespondents. The population in this study is the Blibli.com UPN "Veteran"Consumer in East Java. The sample uses a purposive sampling method. thesampling technique with the characteristics of consumers who have madepurchases at Blibli.com Online Shop 2-3 times. Data analysis techniques in thisstudy used descriptive analysis techniques per variable and multiple linearregression analysis. Based on the results of the analysis using the t test, it is concluded that the E-Service Quality variable partially influences the variable of Minat BeliKonsumen then concluded the Price variable partially effect on Minat BeliKonsumen, Based on the results of the analysis using the F Test, the E-Service Quality,Brand Image and Harga variables were jointly and simultaneously influentialand significantly affected the Blibli.com Online Shop Minat Beli Konsumen inthe research case in the UPN "Veteran East Java consumer environment. Keywoord :E-Service Quality, Brand Image, Harga, Minat Beli Konsumen  DOI : https://doi.org/10.33005/jbi.v12i1.2596